Simulasi Numerik Perkuatan Lentur Balok T yang Mengalami Retak Awal Menggunakan CFRP (Carbon Fiber Reinforced Polymer) - Andhika Mahendra (SONDIR, 2025)
Substandard structural maintenance and natural disasters could impair the structure. However, numerous structures could still be utilized even though the safety level and load capacity diminished. Thus, the structure members needed to be strengthened. One of the most widely applied solutions was the use of Carbon Fiber Reinforced Polymeric (CFRP). CFRP was made from fiber and carbon that can increase the capacity of structure. Therefore, numerical simulation of T-beam strengthened with CFRP in flexural area was important. Because a good agreement results of numerical simulations compared with experimental could reduce cost where numerical simulations could be a tool to carry out further parameter studies without experimental testing. The purpose was to perform a numerical simulation validated by experimental testing from Mulyanto (2020). ABAQUS software was used for simulation. The idealized components included concrete beams, loads, and supports represented as 3D solid elements. The reinforcing steel was modeled as a truss element and conventional shell element was used for modeling CFRP. The model’s dimensions and loading were based on experimental. Factors such as the strength of reinforcing steel, the number of layers of composite layers, and the interaction between concrete and CFRP were utilized to align the experimental results. The results showed that the difference of yield and ultimate load between numerical simulation and the experimental was less than 5%. Therefore, the result of numerical simulation had a good agreement with the experimental.